2015
DOI: 10.3109/09553002.2015.1096028
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-378g enhanced radiosensitivity of NPC cells partially by targeting protein tyrosine phosphatase SHP-1

Abstract: MiR-378g enhanced radiosensitivity partially by targeting SHP-1 in NPC cells. Cell invasion was also partially inhibited by miR-378g, but the effect was not mediated by SHP-1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 37 publications
2
19
0
Order By: Relevance
“…The radiosensitivity in NPC cells is also regulated by miRNAs. For instance, miR-24 [11,12] and miR-378g [13] can enhance the radiosensitivity of NPC cells. This provides evidence for a new clinical therapy treatment for NPC that combines radiation therapy with miRNA regulation in order to enhance the effects of treatment.…”
Section: Introductionmentioning
confidence: 99%
“…The radiosensitivity in NPC cells is also regulated by miRNAs. For instance, miR-24 [11,12] and miR-378g [13] can enhance the radiosensitivity of NPC cells. This provides evidence for a new clinical therapy treatment for NPC that combines radiation therapy with miRNA regulation in order to enhance the effects of treatment.…”
Section: Introductionmentioning
confidence: 99%
“…miR-222 confers radioresistance in NPC cells. It is well established that certain miRNAs can regulate the radioresistance of cancer cells (11)(12)(13)17,18). Thus, the effect of miR-222 on NPC cell radioresistance was investigated.…”
Section: Mir-222 Overexpression Increased Cell Viability and Colony Fmentioning
confidence: 99%
“…Growing evidence supports the critical role of miRNAs in the progression of human cancers, where they function as either oncogenic miRNAs (oncomirs) or tumor suppressors through the regulation of cellular proliferation, differentiation and apoptosis (8)(9)(10). A number of studies have demonstrated that miRNAs are involved in cellular ionizing radiation (IR) responses through cell cycle regulation and the apoptosis signal pathway in several types of cancer, including NPC (11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…It is reasonable to infer that porcine miR-378/G shared some key function with human miR-378 g, e.g. regulation in cancer resistance [35]. So our results in functional analysis of ssc-miR-378/G might also provide some prospect on study about hsa-miR-378 g. In our investigation of the topically relevant literature, only one report was found describing a target gain related to an miRNA SNP the miRNA seed region modify mRNA targeting, cause loss and gain of targeting [33], and are associated with diseases [11,12].…”
Section: Discussionmentioning
confidence: 99%